Pengembangan Media Web Figma untuk Meningkatkan Pemahaman Siswa Mengenai Materi Pemrograman Absolut CNC Milling - Mohamad Rendy Irfansyah; Ari Dwi Nur Indriawan Musyono (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to develop and evaluate the feasibility and effectiveness of a web-based learning media using Figma on the topic of absolute manual programming in CNC Milling. This research employed a Research and Development (R&D) method with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The subjects of this study were 71 students of grade XI Mechanical Engineering at SMK Negeri 1 Semarang, while the preliminary study was conducted with grade XII students who had completed the relevant study period, and the product implementation was carried out with grade XI students as the primary subjects. Data were collected through expert validation sheets, questionnaires, and pretest-posttest instruments. The results showed that the developed media achieved a high level of validity, with scores ranging from 82.5% to 95%, categorized as "very feasible." The practicality of the media was also rated highly, indicated by positive responses from teachers and students with a percentage of 96%. Furthermore, the effectiveness test revealed a significant improvement in students conceptual understanding, supported by paired sample t-test results with a significance value of 0.000 (p < 0.05). The N-Gain scores were 0.84 (small scale) and 0.78 (large scale), both categorized as high. Therefore, the web-based learning media developed using Figma is considered valid, practical, and effective in improving students' understanding of abstract CNC Milling programming concepts through interactive and visual learning.